CYTOFUNCTIONAL DESCRIPTION OF MASTOTSTIV IN THE GUMS OF PATIENTS WITH GENERALIZED PERIODONTITIS - Gasyuk, N.V.; Yerochenko, G.A.; Ivanickiy, I.A.; Gerasimenko, S.B. (World of Medicine and Biology, 2013)
The article presents data concerning the characteristic of functional chants of mast cells in the focus of inflammation in the gums of patients with generalized periodontitis. Through analysis of previous studies which demonstrated that mast cells provide output inflammatory mediators - biologically active compounds, considered as a trigger of inflammation and determines the further course of the inflammatory response, reached the following conclusion that the leading role in the allocation of inflammatory mediators play mast cells and provide it inflammatory phase of inflammatory and degenerative changes in the periodontal tissues.
Keywords: mast cells; gums; periodontitis; mediators of inflammation